A quantitative evaluation of the European commiccion's fiscal governance proposal - Zsolt M. Darvas; Lennard Welslau; Jeromin Zettelmeyer (Bruegel, 2023)
In the new European Union fiscal framework proposed by the European Commission in April 2023, medium-term fiscal adjustment requirements would be determined by country-by-country debt sustainability analysis (DSA), the 3 percent deficit ceiling and simple rules requiring minimum deficit and debt adjustments ("safeguards"). These elements are controversial, with some EU countries (and ourselves) preferring a DSA-based approach, while others prefer to stick to simple rules. This paper evaluates the proposal by replicating the DSA methodology and computing fiscal adjustment implications for all EU countries with debt above 60 percent or deficits above 3 percent of GDP. We find that the proposed framework would require ambitious fiscal adjustment: on average, more than 2 percent of GDP over the medium term, in addition to the adjustment that is already planned for 2023-24. However, for most high-debt countries, these requirements are below those implied by the current framework. We also find that for most countries with debt above 60 percent of GDP, these adjustment requirements are driven by the DSA rather than the safeguards, but with significant exceptions. The main exception is France, for which the "debt safeguard" - which requires debt to fall within four years - imposes much higher fiscal adjustment than the DSA. If the adjustment period were to be extended from four to seven years (as is possible under the framework for countries that submit growth-enhancing reform and investment plans), the safeguards would also be binding for several other countries. In addition, a requirement to reduce the deficit by at least half a percent per year if it exceeds 3 percent of GDP could become binding ex post, in response to output shocks, even if countries implement the fiscal adjustment required ex ante. Finally, we find that while the Commission's DSA methodology is reasonable, it would benefit from review. This should be done by an independent expert group in consultation with the Commission, member states and other stakeholders, and endorsed by the Council. We recommend the endorsement of the Commission's proposal after ambiguous aspects are clarified, the debt safeguard and other safeguards are removed or modified, the excessive deficit procedure is reformed to avoid procyclical adjustment, and a process for reviewing the DSA methodology is put in place.
Keywords: 330; fiscal policy; European semester and fiscal rules